The impact of the European Union-South Africa free trade area agreement on factor returns in South Africa: much ado about nothing? - Chauke, Thabo (School of Economics, 2023)
The notion that the returns of unskilled labour in developed countries are adversely affected by growth in trade with developing countries as a result of trade liberalisation has received a great deal of attention. What underpins this notion is the standard trade theory which posits that trade is determined by factor endowments; hence, trade liberalisation will benefit the relatively abundant factors of production. Since developed countries are relatively abundant in capital and skilled labour, the theory predicts that capital and skilled labour will benefit from trade liberalisation whilst the returns of the scarce factor, unskilled labour, would decline in relative terms. This will increase inequality in the returns of capital and labour or skilled- and unskilled-workers in developed countries. The converse will prevail in developing countries where trade liberalisation stands to reduce wage inequality. What becomes germane to the discussions is that trade liberalisation gives rise to winners and losers. Thus for trade liberalisation to be of mutual benefit, winners must compensate losers for their loss.